Aggregate Productivity Effects of Technology Shocks in a Model of Heterogeneous Firms: The Importance of Equilibrium Adjustments - Erling Holmøy; Torbjørn Hægeland (Statistics Norway, Research Department, 1997)
This paper studies how productivity shifts at the level of the firm are transmitted to aggregate industry productivity in a model of heterogeneous firms. We analyse both uniform productivity shifts, and catching up by reducing the productivity differentials between firms. The two kinds of shifts affect aggregate productivity in different ways and through different mechanisms. Endogenous equilibrium adjustments play a crucial role for the influence on aggregate productivity. Moreover, when firms sell their output to several markets, and their market power differs between markets, aggregate productivity may be inversely related to productivity at the firm level. A by-product of the analysis is to demonstrate that productivity heterogeneity can be incorporated in the standard model of monopolistic competition at a low cost in terms of analytical tractability.
Keywords: D24; L11; 330; Productivity; Heterogeneity; Aggregation; Monopolistic competition